2011
DOI: 10.1097/bot.0b013e3181db703c
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Team Approach to Improve Postoperative Hip Fracture Care

Abstract: The addition of a calcium/vitamin D supplement and an endocrinology appointment to the hospital discharge orders was an effective method of improving treatment and enhancing compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…[ 20 ] Increasing rate of osteoporosis medication in patient with hip fracture use beyond 6 months of the intervention ranged from 16% to 34.1% ( Table 2 ). [ 14 15 16 17 18 19 ] Our findings are corresponded with other previous reports. In this study, comparing with control group, increasing rate of anti-osteoporosis medication was increased by 17.2% and medication persistence was 40.2% at the 12 months follow-up.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[ 20 ] Increasing rate of osteoporosis medication in patient with hip fracture use beyond 6 months of the intervention ranged from 16% to 34.1% ( Table 2 ). [ 14 15 16 17 18 19 ] Our findings are corresponded with other previous reports. In this study, comparing with control group, increasing rate of anti-osteoporosis medication was increased by 17.2% and medication persistence was 40.2% at the 12 months follow-up.…”
Section: Discussionsupporting
confidence: 92%
“…Several interventional studies for improving osteoporosis management following hip fracture have demonstrated that patients and/or physicians education can lead to improvement of initiation rate of anti-osteoporosis medications in patients with hip fracture. [ 14 15 16 17 18 19 ] Previously, we performed interventional study for improving orthopaedic surgeon awareness and reported an improved medication rate of osteoporosis from 15% to 32% in patients with hip fracture. [ 12 ] However, 32% of the osteoporosis treatment rate at six months following hip fracture was still lower than other intervention studies.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies that demonstrate that coordination between the orthopedic and endocrinology services, especially with outpatient management, leads to improved outcomes. 8 , 13 , 28 - 31 One system that has shown success has been the Kaiser Southern California Healthy Bones Program. The deployment of an aggressive bone health program that facilitated the management of osteoporosis in patients with recent fragility fractures with the referral of complex patients to endocrinology was able to reduce the number of hip fractures by 37%.…”
Section: Discussionmentioning
confidence: 99%
“…¤ A prospective cohort study evaluated the effect of multispecialty inpatient care on the treatment of osteoporosis in 137 patients with a hip fracture 20 .…”
Section: Femurmentioning
confidence: 99%